Effects of nitrogen ion irradiation on plasma polymerized films produced from titanium tetraiso pro poxide-oxygen-helium mixtures - Da Cruz, Nilson C. [UNESP]; Lopes, Bruno B. [UNESP]; Rangel, Elidiane C. [UNESP]; de Moraes, Mario A. B.; Durrant, Steven F. [UNESP] (Elsevier B.V. Sa, 2008)
In this work films were produced by the plasma enhanced chemical vapor deposition (PECVD) of titanium tetraisopropoxide-oxygen-helium mixtures and irradiated with 150 keV singly-charged nitrogen ions (N(+)) at fluences, phi, between 10(14) and 10(16) cm(-2). Irradiation resulted in compaction, which reached about 40% (measured via the film thickness) at the highest fluence. Infrared reflection-absorption spectroscopy (IRRAS) revealed the presence of Ti-O bonds in all films. Both O-H and C-H groups were present in the as-deposited films, but the density of each of these decreased with increasing phi and was absent at high phi, indicating a loss of hydrogen. X-ray photoelectron spectroscopy (XPS) analyses revealed an increase in the C to Ti atomic ratio as phi increased, while the O to Ti ratio hardly altered, remaining at around 2.8. The optical gap of the films, derived from data obtained by ultraviolet-visible spectroscopy (UVS), remained at about 3.6 eV for all fluences except the highest, for which an abrupt fall to around 1.0 eV was observed. For the irradiated films, the electrical conductivity, measured using the two-point method, showed a systematic increase with increasing phi. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Thin films; Ion irradiation; PECVD; XPS; Ti